Fiscal Expenditure Policy and Non-Oil Economic Growth : Evidence from GCC Countries - Wang, Qing (IMF Working Papers; Working Paper ;, 2001)
Through the use of a multivariate cointegration and error-correction model, this study investigates the short- and long-run relationship over the past two decades between fiscal expenditure policy and non?oil real GDP growth in member countries of the Gulf Cooperation Council (GCC). Despite the important role of the government, the empirical results do not strongly support that increases in fiscal expenditures tend to slow or accelerate non?oil real growth in these countries. However, the breakdown into current and capital expenditures is useful for assessing the effects of each spending category on short- and long-run non?oil real GDP growth.